Validity of Green Chemistry Student Worksheet Based on Project Based Learning for Phase E at SMAN 9 Padang - Rani, Wahyu Mustika; Iryani, Iryani (Jurnal Pendidikan dan Pembelajaran Kimia, 2023)
The project-based chemistry learning process can be carried out by studying phenomena in the surrounding environment so that students are interested and actively involved in solving problems given by the teacher related to chemical concepts. One of the alternative teaching materials that can be used as support is Student Worksheet. This study aims to determine the validity category of project-based learning-based green chemistry student worksheets for phase E at SMAN 9 Padang that have been developed. This type of research is Educational Design Research (EDR) using the Plomp development model. Plomp's development model consists of the stages of preliminary research, prototyping and assessment, but in this study it is limited to the prototype III stage. The validity instrument used was a questionnaire consisting of content and construct validity. The results of the validity in this study obtained an average V value of 0.85 with the valid category. Based on these results, it can be concluded that the student worksheets developed are valid. DOI: 10.23960/jppk.v12.i3.2023.12